Integration of Peace Theology in the Christian Education Curriculum: Challenges and Opportunities - Benyamin Dadi Ratu Mofu (Teaching and Learning Journal of Mandalika (Teacher) e- ISSN 2721-9666, 2025)
The research is carried out with the intention of discovering and underlining the necessity of the support of peace theology with the setting of Christian education to make possible the formation of peace oriented congregations. It is in fact the young people who at the same time represent the solution and the problem of the contemporary reality. Peace is presented as one of the major cornerstones in front of the rapid environment and therefore imparting it in the very young age is essential. The research brings out two major issues: the problems that are hard to confront while integrating theology into the Christian education and the possibilities that arise making this process. Using a qualitative approach, data was collected through literature studies. The study was aimed at informing the readers about both the tough and the easy sides of the matter and at the same time, to propose solutions for those problems to the people Involved in the education of Christian education in the social sphere. This research is expected to make a significant contribution to the development of a Christian education curriculum that focuses more on peace values